1995
DOI: 10.1525/9780520310315
|View full text |Cite
|
Sign up to set email alerts
|

The Romance of American Psychology

Abstract: We must admit that the rapid growth of psychology in America has been due to conditions of the soil as well as the vitality of the germ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 626 publications
(22 citation statements)
references
References 4 publications
0
21
0
1
Order By: Relevance
“…The minutes from its first meeting on August 1, 1967, indicate that an inquiry about the availability of Kenneth A. Clark whose research on race and self-perception was cited by the Supreme Court in its landmark Brown v. Board of Education ruling had been made, 94 and it has been reported that other prominent sociologists, like James Coleman, who had conducted a major federal study on the equality of educational opportunities, were approached but that they declined either because the fall semester was about to begin and they had teaching commitments to honor or they were concerned that the Commission's final report would be "a whitewash." 95 However, although Robert Shellow was not the Commission's first choice to lead its research team, he had been recommended by Arthur Brayfield of the American Psychological Association 96 and he had been interviewed by a group of senior staff and Commission members that included Ginsburg, Palmieri, the Commission's chairman, and the Commission's vice chairman. Also, several "Harvest"-related articles written by Shellow, Goldberg, Marx, and Boesel just a couple of years after their work at the Commission provide an indication of what they were capable of doing with a little more time, less pressure, and a little more experience.…”
Section: Could the Controversy Have Been Avoided?mentioning
confidence: 99%
“…The minutes from its first meeting on August 1, 1967, indicate that an inquiry about the availability of Kenneth A. Clark whose research on race and self-perception was cited by the Supreme Court in its landmark Brown v. Board of Education ruling had been made, 94 and it has been reported that other prominent sociologists, like James Coleman, who had conducted a major federal study on the equality of educational opportunities, were approached but that they declined either because the fall semester was about to begin and they had teaching commitments to honor or they were concerned that the Commission's final report would be "a whitewash." 95 However, although Robert Shellow was not the Commission's first choice to lead its research team, he had been recommended by Arthur Brayfield of the American Psychological Association 96 and he had been interviewed by a group of senior staff and Commission members that included Ginsburg, Palmieri, the Commission's chairman, and the Commission's vice chairman. Also, several "Harvest"-related articles written by Shellow, Goldberg, Marx, and Boesel just a couple of years after their work at the Commission provide an indication of what they were capable of doing with a little more time, less pressure, and a little more experience.…”
Section: Could the Controversy Have Been Avoided?mentioning
confidence: 99%
“…During World War II, the three main contributions of American psychologists to the war effort were the psychological screening of military personnel, psychotherapy for war victims, and research into morale. After the war, these fields served as the springboard for a surge in psychometry, psychotherapy, and social psychology, respectively (Herman, 1995). Unlike the Americans, Soviet psychologists were involved mainly in treating neurological damage suffered by the battle-wounded, and to some extent in solving the military's technical problems; this was the case with Boris Ananyev, who took part in designing new camouflage schemes to hide buildings from enemy aircraft (Kol'tsova and Oleinik, 2006).…”
Section: Theories As Expressions Of Epochsmentioning
confidence: 99%
“…She later realized it was part of a familiar historical pattern: women struggling for equal rights (and acknowledgment) in a male-dominated field. Adding to the saliency of Calkins's shabby treatment in the 1890s was the Harvard psychology department's treatment of female graduate students as second-class citizens in the 1960s (Herman, 1995;Lewin, 1992).…”
mentioning
confidence: 99%